The finite-time ruin probabilities of a dependent bidimensional risk model with subexponential claims and Brownian perturbations - Xu, Chenghao; Shen, Xiaowen; Wang, Kaiyong (Nonlinear Analysis: Modelling and Control, 2025)
The paper considers a dependent bidimensional risk model with stochastic return and Brownian perturbations in which the price processes of the investment portfolio of the two lines of business are two geometric Lévy processes, and the claim-number processes of the two lines of business follows two different stochastic processes, which can be dependent. When the two components of each pair of claims from the two lines of business are strongly asymptotically independent and have subexponential distributions, the asymptotics of the finite-time ruin probability are obtained. Numerical studies are carried out to check the accuracy of the asymptotics of the finite-time ruin probability for the claims having regularly varying tail distributions.